KLASIFIKASI TAFSIR PERSPEKTIF WALID A. SALEH: Telaah pada Kitab Tafsir Al-Kasyf wa al-Bayān ʿan Tafsīr Al-Qurʾān Karya Imam al-Thaʿlabī - Rezwandi Rezwandi; Ahmad Fikri (TAFAKKUR : Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
This study discusses the classification of tafsir according to Walid A. Saleh's perspective, focusing on an analysis of al-Thaʿlabī's book Tafsir al-Kasyf wa l-bayān. The main objective is to map the position and contribution of al-Thaʿlabī's tafsir in the classical tafsir tradition through a conceptual approach developed in his work The Formation of the Classical Tafsir Tradition. This study uses a qualitative library research method with a character study approach, which relies on the analysis of primary and secondary texts related to tafsir and the thoughts of Walid A. Saleh. The results show that Saleh classifies tafsir works into three main categories: First, encyclopaedic tafsir (muṭawwalāt al-tafsīr). Second, madrasah tafsir. Third, Hāsyiyah madrasah tafsir. These three categories reflect different functions and levels of understanding in the interpretation process. Saleh also criticises previous models of tafsir classification, such as those proposed by al-Dzahabi, Ignaz Goldziher, and John Wansbrough, which he considers to be insufficiently comprehensive and overly reductionist. Through the concept of ‘tafsir as a genealogical tradition,’ Saleh emphasises that every work of tafsir is the result of a dialectic with previous tafsir traditions. His idea enriches the discourse of tafsir historiography and offers a new paradigm that is more historical, dialogical, and contextual in understanding the development of Qur'anic tafsir.